Visual Odometry Using Pixel Processor Arrays for Unmanned Aerial Systems in GPS Denied Environments - McConville, Alexander; Bose, Laurie; Clarke, Robert; Mayol-Cuevas, Walterio; Chen, Jianing; Greatwood, Colin; Carey, Stephen; Dudek, Piotr; Richardson, Tom (Frontiers in Robotics and AI, 2020)
Environments in which GPS signals cannot be received pose problems for the control and guidance of robots. These might include operations underground, underwater or in hostile GPS-denied areas. Pixel Processor Array (PPA) cameras - in conjunction with other sensors - can be used to address the problem of establishing location, tracking and control. In this paper we use a PPA - the SCAMP vision chip - to demonstrate the marriage of perception and compute capabilities on the same device for the purposes of real-time navigation and control of aerial robots. A PPA consists of a parallel array of Processing Elements (PEs), each of which features light capture, processing and storage capabilities. This allows various image processing tasks to be efficiently performed directly on the sensor itself. Within this paper we demonstrate visual odometery and target identification running sequentially on-board a single PPA vision chip at frame rates in the region of 400\,Hz. Results are given for outdoor multirotor test flights, with comparisons shown against the baseline GPS results. This capability to run multiple algorithms at adaptive rates, in conjunction with the High Dynamic Range (HDR) of the SCAMP PPA provides a sensor that is well suited to addressing the challenge of outdoor Small Unmanned Aerial Systems (SUAS) flight in GPS denied environments. HDR can be used in situations where there is a rapid transition from indoor to outdoor environments, and images in which there are significant variations in light level across a single frame. Additionally, the PPA only needs to output specific information such as the optic flow and target position, rather than having to output entire images. This significantly reduces the bandwidth required for communication between the sensor and on-board flight computer, further enabling a high frame rate and low power operation. In future applications, multiple SCAMP PPAs could be used to provide wide angle optic flow, target identification and feature tracking within minimal additional overhead penalties in terms of weight and computational requirements.